Insulin-like growth factor system gene expression in women with type 2 diabetes and breast cancer. Issue 8 (30th July 2003) - Nardon, E; Buda, I; Stanta, G; Buratti, E; Fonda, M; Cattin, L
Abstract : Background/Aims: A twofold increased risk for breast cancer has been reported recently for women with late onset diabetes. Most studies showed that there were differences in serum concentrations of insulin-like growth factors and related proteins between women with and without diabetes who have breast cancer. This study investigated the expression of these markers at the cellular level in a cohort of women with and without type 2 diabetes who underwent biopsy because of a breast lump. Methods: Relative quantitative analysis of specific mRNA sequences was performed after extraction and reverse transcription polymerase chain reaction amplification from formalin fixed and paraffin wax embedded tissues. Sixty seven breast surgical specimens from women with and without diabetes who did not have cancer and from women with and without diabetes who did have cancer were studied for insulin-like growth factor I (IGF-I), the IGF-I receptor (IGF-IR), insulin-like growth factor binding protein 3 (IGFBP-3), and oestrogen receptor 1 gene expression. Results: The expression of IGF-I and IGF-IR was significantly lower in the cancer groups, whereas there was no significant difference for IGFBP-3 between women with and without cancer. Moreover, there was a good correlation between the expression of IGF-I and IGF-IR in women without cancer: this link was still present in breast tissue from patients with diabetes and cancer, whereas it was lost in patients without diabetes but with cancer. Conclusions: These differences in IGF-I/IGF-IR expression could contribute to the increased risk for breast cancer in women with type 2 diabetes.